Positive psychology - Hefferon, Kate; Lomas, Tim 1979- (Sage benchmarks in psychology., 2015)
Positive Psychology has evolved rapidly over the past decade, attracting an ever-increasing number of adherents in academia and beyond. In just over 15 years since the emergence of the field, interest has grown exponentially, drawing in both new students and established scholars, generating a proliferation of journal articles and international conferences, and attracting considerable interest in the media and society at large. This major offers a clear and comprehensive assessment of Positive Psychology, assembling the seminal theories, studies and applications together in one overarching compendium and bringing clarity and definition to this emerging discipline.--Taken from Amazon.com®